2023
DOI: 10.1186/s12985-023-01996-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into organoid-based modeling of COVID-19 pathology

Abstract: Since December 2019, various types of strategies have been applied due to the emergent need to investigate the biology and pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to discover a functional treatment. Different disease modeling systems, such as mini-organ technology, have been used to improve our understanding of SARS-CoV-2 physiology and pathology. During the past 2 years, regenerative medicine research has shown the supportive role of organoid modeling in controlling corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 137 publications
(195 reference statements)
1
2
0
Order By: Relevance
“…Our results showed that for Omicron infections, regardless of the variants, the viral load in the nose was significantly higher than that in the oropharyngeal after symptom onset. This is consistent with the replication fitness of Omicron observed in a nasopharyngeal organoids infection model [ 18 , 19 ]. By analyzing the replication dynamics during the entire infection process, we were able to obtain a complete and clear picture of the viral replication kinetics for Omicron variants in the host.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that for Omicron infections, regardless of the variants, the viral load in the nose was significantly higher than that in the oropharyngeal after symptom onset. This is consistent with the replication fitness of Omicron observed in a nasopharyngeal organoids infection model [ 18 , 19 ]. By analyzing the replication dynamics during the entire infection process, we were able to obtain a complete and clear picture of the viral replication kinetics for Omicron variants in the host.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, ibuprofen may indirectly inhibit poly (ADP‐ribose) polymerase 1 (PARP1) by a COX2‐independent effect, 16 since PARP1 inhibition may negatively modulate TMPRSS2 transcription and expression 16 . In addition, a study performed in lung organoids has shown that the ACE2/TMPRSS2 entry route may be the most important internalization pathway of SARS‐CoV‐2, 47 making this route one of the most important and interesting therapeutic targets.…”
Section: Potential Therapeutic Effects Of Naihs In Pneumonia and Card...mentioning
confidence: 99%
“…Moreover, ibuprofen may indirectly inhibit poly (ADP‐ribose) polymerase 1 (PARP1) by a COX2‐independent effect, 16 since PARP1 inhibition may negatively modulate TMPRSS2 transcription and expression 16 . In addition, a study performed in lung organoids has shown that the ACE2/TMPRSS2 entry route may be the most important internalization pathway of SARS‐CoV‐2, 47 making this route one of the most important and interesting therapeutic targets. NaIHS might prevent the reorganisation of actin filaments, 1 avoiding the interaction between the viral S1 protein and host actin 1 by the inhibition of the synthesis and release of the cytokine IL‐1β and the negative modulating of the rock kinase A pathway, 48 through a COX2‐dependent effect 48 . NaIHS might also inhibit the activation of Rho GTPase and its alternatively spliced isoform Ras‐related C3 botulinum toxin substrate 1b, 4 through a COX‐independent effect 4 …”
Section: Potential Therapeutic Effects Of Naihs In Pneumonia and Card...mentioning
confidence: 99%